Health status analysis of Norway spruce and shrubby pine along an elevation gradient - Falvai, Dominika; Baltazár, Tivadar; Czóbel, Szilárd (COLUMELLA – Journal of Agricultural and Environmental Sciences, 2019)
The results of numerous climatic models predict a significant increase in temperature, which co- upled with other factors could affect mountain species distribution and community composition. In addition, it can accelerate an upward shift of alpine treelines. However the number of field measurements focusing on the health status of dominant trees in temperate mountains are limited. Our measurements were carried out in the Stuhleck Mountains along an elevation gradient from 850 to 1750 metres. Health status analysis of Picea abies and Pinus mugo have been completed by using FAKOPP 3D acoustic tomography, which is able to detect the size and location of decayed regions in the trunk non-destructively. For modelling the relati- onship between the decay of tree and other factors simple linear regression models were used. The results showed that the individuals of Picea abies and Pinus mugo had the worst health status in the lowest and up- permost range of the taxa in the studied area. It could be a sign of the upward shift of their range. Positive significant correlation was found between the decay and the ratio of whole trunk/healthy wood both in case of Picea abies and Pinus mugo. It seems, that acoustic tomography measurements are adequate to indicate non-destructively the altitudinal optimum and upward shift of different taxa.